Healthy Aging: A Case Report - Nazish Hussain Ali Pachani; Kiran Shoukat Ali; Armish Aziz; Laila Naushad; Zoya Feroz Ali (International Journal on Women Empowerment, 2016)
The process of aging is considered to be a weakness, disease or death. In reality, this is a myth. In West Virginia the concept of ‘Healthy Aging’ is developed to empower senior members of the country worldwide. This case report illustrates the application of the concept ‘Healthy Aging’ to an institutional setting in Karachi. This group project primarily aimed at how the client thinks, feels, communicates and respond to change in self and environment. The group planned to categorize activities into five components as physical, physiological, psychological, emotional, and spiritual domains. It builds a strong foundation for health promotion and disease prevention in older adults. Clients gain insight and group had an everlasting learning experience in geriatric care.